Autophagy Suppresses Toll-Like Receptor 3-Mediated Inflammatory Reaction in Human Epidermal Keratinocytes. (5th May 2020) - Li, Xue Mei; Jung, Kyung Eun; Yim, Su Hyuk; Hong, Dong Kyun; Kim, Chang Deok; Hong, Jeong Yeon; Lee, Ho Jung; Lee, Sung Yul; Kim, Jung Eun; Park, Chang Wook
Abstract : Autophagy, one mechanism of programmed cell death, is fundamental to cellular homeostasis. Previous studies have identified autophagy as a novel mechanism by which cytokines control the immune response. However, its precise role in immune-related inflammatory skin diseases such as psoriasis remains unclear. Thus, this study explored the functional role of autophagy in psoriatic inflammation of epidermal keratinocytes. Strong light chain 3 immunoreactivity was observed in epidermal keratinocytes of both human psoriatic lesions and imiquimod-induced mice psoriatic model, and it was readily induced by polycytidylic acid (poly (I:C)), which stimulates Toll-like receptor 3 (TLR3), in human epidermal keratinocytes in vitro. Rapamycin-induced activation of autophagy significantly reduced poly (I:C)-induced inflammatory reaction, whereas, inhibition of autophagy by 3-methyladeine increased that. Our results indicate that the induction of autophagy may attenuate TLR3-mediated immune responses in human epidermal keratinocytes, thus providing novel insights into the mechanisms underlying the development of inflammatory skin diseases including psoriasis.